2001
DOI: 10.1007/s002100000393
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of SM-20550, an Na + /H + exchange inhibitor, on accumulation of leukocytes in ischemia and reperfusion

Abstract: The effect of an Na+/H+ exchange inhibitor, SM-20550, on the adhesion, emigration and accumulation of leukocytes was studied in ischemia and reperfusion injury models using rat mesenteric venules or rabbit heart. Anesthetized rats underwent occlusion of the superior mesenteric artery (20 min) followed by reperfusion (60 min). After ischemia and reperfusion, the numbers of adherent and emigrated leukocytes increased significantly. Bolus intravenous administration of SM-20550 reduced the numbers of adherent and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…immediately after initiation of ischemia) reduced total infarction area by ~50%, and partially prevented formation of brain edema [96]. These effects may be relevant to preservation of blood-brain barrier function and improved reperfusion rates [97], as well as to reduced accumulation of leukocytes in damaged brain tissue [98]. In the same model, another selective NHE blocker, sabiporide (3 mg/kg, i.v.…”
Section: Pathological Roles For Na + /H + Exchange: Impact On [Na + ]mentioning
confidence: 95%
“…immediately after initiation of ischemia) reduced total infarction area by ~50%, and partially prevented formation of brain edema [96]. These effects may be relevant to preservation of blood-brain barrier function and improved reperfusion rates [97], as well as to reduced accumulation of leukocytes in damaged brain tissue [98]. In the same model, another selective NHE blocker, sabiporide (3 mg/kg, i.v.…”
Section: Pathological Roles For Na + /H + Exchange: Impact On [Na + ]mentioning
confidence: 95%
“…The most important factor influencing patient mortality and morbidity is the extent of myocardial necrosis. Many laboratories have documented reduced infarct sizes with a variety of NHE inhibitors in short‐term animal models (4–9). Rupprecht et al reported significantly reduced enzyme release during the first 72 hours postreperfusion in their small patient group; however, results from Théroux et al's GUARDIAN clinical trial indicate that there were no benefits, in the trial as a whole, at 36 days, in the endpoints of death or myocardial infarction (16, 25).…”
Section: Discussionmentioning
confidence: 95%
“…This study investigated the effects of cariporide in the canine heart following a reperfused ischemic insult. NHE inhibitors have been well documented as cardioprotective agents in short‐term ischemia/reperfusion models (4–11, 23, 24). However, to our knowledge, this is the first study of the long‐term effects of a high dose of cariporide in an animal infarct model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations